Language Use and Media Framing in the Pertamina Corruption Case in National and International Media - Alfelia Nugky Permatasari; Erlin Estiana Yuanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
The mass media plays a crucial role in shaping public perceptions of corruption through language choices and framing strategies. This study examines how The Jakarta Post and Reuters reported the Pertamina corruption case using linguistic and framing analysis. A qualitative Thematic Analysis supported by ATLAS.ti was applied to identify dominant themes, guided by Media Framing theories. The dataset comprised online news articles published within six months of the report, February-July 2025, each exceeding 200 words and focusing explicitly on the case. The findings reveal that The Jakarta Post employed moral and social framing centered on public accountability, while Reuters adopted legal and institutional framing emphasizing procedural neutrality and institutional credibility. These contrasts highlight differing orientations and journalistic functions: The Jakarta Post aligns with advocacy-driven national media, whereas Reuters represents objectivity-centered international journalism.